Demanda residencial por eletricidade no Paraná : um estudo utilizando dados em painel - Kamitani, Eder Luis Tomokazu (2012)
Electricity is a commodity whose production and consumption occur simultaneously due to the characteristics of good. Thus, is salutary to understand the behavior of electricity demand for that supply is sufficient, without waste or outages. The main objective of this study is to estimate the income elasticity and price elasticity for residential demand for electricity. Thus, the study uses a database panel of 399 municipalities of Paraná, for the period 1999-2009. The use of the methodology allows you to control individual effects for the municipalities and their intrinsic characteristics. Two methods were used: panel data fixed effects and random effects. In addition, models were run with dummies for the years and for geographica l mesorregion. The results showed a better adjustment of panel data models, supporting the idea that local factors may influence the residential demand for electricity. The income elasticities and price elasticities obtained show low influence of price and income in residential. consumption of electricity